Scholarly productivity of faculty in primary care roles related to tenure versus non-tenure tracks - Braxton, Michaela M. (BMC Med Educ, 2020)
BACKGROUND: Increasing the number of primary care physicians is critical to overcoming the shortage of healthcare providers. Primary care physicians are increasingly called upon to address not only medical concerns but also behavioral health needs and social determinants of health which requires ongoing research and innovation. This paper evaluated scholarly productivity of faculty in tenure versus non-tenure tracks in primary care roles, defined as family medicine, internal medicine, internal medicine/pediatrics and pediatrics. METHODS: The study included physician faculty in the clinical departments of Brody School of Medicine serving between the 2014–2015 and 2018–2019 academic years. Department, track, and rank at the beginning of each academic year (e.g., 2014–2015) were correlated with having any publications in the following calendar year (e.g., 2015), as determined from a search of the Scopus database. RESULTS: A total of 1620 observations and 542 unique faculty were included in the analysis. As of 2018–2019, 19% percent of primary care faculty were either tenured or on tenure track, as compared to 41% of faculty in other departments (p < 0.001). Primary care departments were also disproportionately staffed by junior faculty (60% as compared to 48% in other departments; p = 0.087). The proportion of faculty with any publications was significantly higher for faculty on the tenure track compared to those not on the tenure track (34% vs. 14%, p < 0.001). CONCLUSIONS: Academic productivity was lower among non-tenure-track physician faculty, as measured by publication in peer-reviewed journals. This was exacerbated among faculty in primary care departments, who were also more likely to hold non-tenure-track appointments. The loss of tenure-track positions disproportionately impacts scholarly activity in primary care and may be limiting progress in care-oriented research. Findings suggest that providing non-tenure faculty the time and resources to be involved in research, in addition to their clinical work, as well as access to research collaborators and mentors can promote scholarly activity among this group.